Shanoir: Applying the Software as a Service Distribution Model to Manage Brain Imaging Research Repositories - Barillot, Christian; Bannier, Elise; Commowick, Olivier; Corouge, Isabelle; Baire, Anthony; Fakhfakh, Ines; Guillaumont, Justine; Yao, Yao; Kain, Michael (Frontiers in ICT, 2016)
Two of the major concerns of researchers and clinicians performing neuroimaging experiments are managing the huge quantity and diversity of data and the ability to compare their experiments and the programs they develop with those of their peers. In this context, we introduce Shanoir, which uses a type of cloud computing known as software as a service (SaaS) to manage neuroimaging data used in the clinical neurosciences. Thanks to a formal model of medical imaging data (an ontology), Shanoir provides an open source neuroinformatics environment designed to structure, manage, archive, visualize and share neuroimaging data with an emphasis on managing multi-institutional, collaborative research projects. This article covers how images are accessed through the Shanoir Data Management System and describes the data repositories that are hosted and managed by the Shanoir environment in different contexts.